The Relationship of Knowledge and Family Support with the Compliance of the Diet of Patients with Diabetes Mellitus - M Ramadhani Firmansyah; Lisa Rizky Amalia; Rahayu Tri Nuritasari; Ana Fitria Nusantara; Yoanita Hijriyati (CV. Get Press Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease requiring long-term management, particularly through adherence to dietary recommendations to maintain blood glucose stability and prevent complications. Nevertheless, many patients show poor compliance with dietary guidelines. This study aimed to determine the relationship between patients’ knowledge, family support, and dietary adherence in DM management. A quantitative cross-sectional design was employed with 75 outpatients at Ambacang Health Center, selected through purposive sampling. Data collection used standardized and validated questionnaires, and analysis was performed using the chi-square test. The results demonstrated significant associations between knowledge and dietary compliance (p = 0.012) as well as between family support and dietary compliance (p = 0.001). Patients with higher knowledge and stronger family support were more likely to adhere to dietary recommendations. These findings emphasize the importance of educational interventions involving both patients and families. Family support in emotional, motivational, and practical aspects enhances commitment to following dietary plans. In conclusion, adequate knowledge and strong family support play crucial roles in improving dietary adherence among DM patients. Healthcare providers are encouraged to provide ongoing education for both patients and families to strengthen adherence to dietary management and optimize diabetes care outcomes.